Awareness on Consumer Finance in Rural Market: An Analysis - Nandagopal, R.; Chinnaiyan, P. (Indian Journal of Marketing, 2005)
Indian rural market is very large and diverse.It grows at the rate of four percent and introduces 1.2 million new consumers every year. In India 620 million rural populations,living in 6.25 lakh villages use the services of 36.98 lakh rural retail outlets. Consumer finance is that part of financing that provides the assistance to buy consumer electronics and durables. It is one of the potential areas of growth. It indirectly helps in the increase in sales of durables. Companies are increasingly using consumer financing as a marketing tool. It serves as an incentive to consumers to upgrade their products, go in for multiple product options etc. With payment being phased out over a few months, it is more manageable for a household compared with a one time payment. In addition to dealers offering their own installment schemes, several consumer financing institutions have come up, facilitating the purchase of consumer durables and thus leading to their demand growth.